Tutorial Submit Articles on the Open Journal System (OJS) - Chandra Prasadhita; Galih Fajar Muttaqin; Dabella Yunia (EQUATOR SINAR AKADEMIA, 2021)
Submitting articles to the Online Journal System (OJS) has been seen as a difficult thing for the public. The proposed community service program is a community service program that aims to provide easy solutions for the community to publish research results. The public can take advantage of technology to publish works through the Open Journal System (OJS). Based on the background of the proposer team and the experience of the proposer team, hereby, the team proposes a community service program with the theme